The Development of Ternary TiO2/ZnS/g-C3N4 Photocatalyst with Enhanced Photodegradation of Organic Pollutants Under Visible Light - Aneshaa, Chandrasekaran (Journal of Materials Science, 2024)
The photocatalytic degradation efficiency of titanium, TiO2-based photocatalysts is limited, especially under visible light. To enhance their efficiency, ternary composites can be created by combining TiO2 with other photocatalysts which are graphitic nitride (g-C3N4) and zinc sulphide (ZnS). To investigate the photocatalytic efficiency for the degradation of single and mixed pollutants under visible light, a ternary TiO2/ZnS/g-C3N4 photocatalyst was synthesised using a facile hydrothermal method. Various characterisation techniques were employed to evaluate the surface area, morphology, crystallinity, and optical and elemental properties via x-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy with energy-dispersive x-ray spectroscopy (FESEM-EDX), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET), and ultraviolet-visible diffuse reflectance spectroscopy (UV-DRS), respectively. The optimal g-C3N4 loading in the TiO2/ZnS/g-C3N4 ratio was determined through several ratios (1:1:X), where X represents different quantities of g-C3N4 (in g): X = 0.3, 0.5, 0.7, 1, and 2. The highest removal rate of 89.9% of Rhodamine B, RhB was achieved using g-C3N4 loading of 1 g, resulting in a TiO2/ZnS/g-C3N4 ratio of 1:1:1. The synthesised ternary TiO2/ZnS/g-C3N4 (1:1:1) photocatalyst exhibited enhanced absorption in the visible light region compared to the pristine TiO2. Under visible light exposure, the ternary photocatalyst efficiently removed approximately 90% of RhB (10 mg/L) within 180 minutes. Moreover, in the presence of mixed pollutants, the ternary photocatalyst simultaneously eliminated 82.7% of RhB, 78.2% of methyl orange (MeO), and 62.2% of 2-chlorophenol (2CP) within a similar treatment time. Further investigations determined an optimal dosage of 1 g/L for the 1:1:1 ratio ternary TiO2/ZnS/g-C3N4 composite. Additionally, the optimal initial RhB concentration for achieving maximum efficiency was found to be 10 mg/L. In the case of the iv effect of pH study, the highest RhB degradation efficiency (89.9%) was observed at an unadjusted pH of 7.2, followed by pH 10 (85.4%) and pH 7.0 (82.5%), while the lowest degradation was observed at pH 3 (72.4%). After four cycles of recycling, a slight decrease in RhB degradation from 89.9% to 86.6% was observed, indicating improved stability and recycling capabilities of the ternary photocatalyst. The successful synthesis and application of the ternary TiO2/ZnS/g-C3N4 photocatalyst, along with its efficient degradation of both individual and mixed pollutants, demonstrate its significant potential for sustainable wastewater treatment.